Dermoscopic findings of nevus sebaceous. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case 1. A 13-month-old little girl was first observed due to the presence of an alopecic area from birth. The physical examination showed an area of alopecia on the vertex, flat, pink-yellowish, regularly and finely granular (Fig. 1) leading to the final diagnosis of nevus sebaceous. The diagnosis was confirmed by dermoscopy showing yellowish lobules, rounded, of uniform diameter, with a few thin hairs (Fig. 2). Case 2. A 7-year-old child was visited for the first time due to an area of alopecia of the scalp present from birth. The dermatological examination showed on the vertex a just raised plaque with irregular edges, warty surface and very few thin hair (Fig. 3). These clinical features led to the final diagnosis of warty nevus sebaceous. Dermoscopy showed lobules of comedo-like structures with sparse and thin hair (Fig. 4).